Skill Teaching Competencies for Working in Virtual Learning Communities - Gordon Graell, Roberto (2022)
Virtual education is a sign of modern times. As an intentional social phenomenon, it complies with the general characteristics of education, but the specificity of its medium marks it with its own characteristics related to virtuality, technology and increasingly shorter disruption in time. The process is affected by social, technical, procedural and functional causes for which the teaching role plays a fundamental role in order to achieve a meaningful, effective and quality teaching-learning process to carry out the functions and achieve the educational objectives. The Latin American reality is that university teachers are at a disadvantage since most of them are digital migrants. More than a technical disadvantage, it is a weakness of perception that is only slightly addressed in the specialized literature. The objective of this article is to analyze the basic affective and perceptual competencies that a teacher must develop to become a facilitator of virtual learning communities. A literature review focused on virtual education and the necessary role of today's university teacher was carried out in the understanding that we are not yet in the foreseen future of a total digital native society.